2017
DOI: 10.1002/2016jc012436
|View full text |Cite
|
Sign up to set email alerts
|

Coastal‐trapped behavior of the diurnal internal tide at O'ahu, Hawai'i

Abstract: The influence of rotation on the structure and propagation of internal tides around O'ahu, Hawai'i is investigated using in situ observations and a tidally forced, primitive equation model with realistic bathymetry and stratification. Particular attention is given to the diurnal internal tide, which largely has been de‐emphasized in previous studies of the region because of the dominance of the semidiurnal internal tide but has been determined by recent studies to be a significant contributor to baroclinic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Using the Princeton Ocean Model, Carter et al () estimate that 85% of the semidiurnal barotropic tidal energy lost over the Hawaiian Ridge is converted into internal tides. The energy flux of the semidiurnal internal tide is an order of magnitude larger than that of the diurnal internal tide (Smith et al, ). Specifically, given that our study site is near Kaena Ridge, observed to generate intense internal tides (Nash et al, ), it is likely that the measured pressure gradients and the resulting velocities are primarily driven by the evanescent tail of the M 2 internal tide propagating in deeper stratified waters offshore, which influences the nearshore region, despite the lack of local stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Princeton Ocean Model, Carter et al () estimate that 85% of the semidiurnal barotropic tidal energy lost over the Hawaiian Ridge is converted into internal tides. The energy flux of the semidiurnal internal tide is an order of magnitude larger than that of the diurnal internal tide (Smith et al, ). Specifically, given that our study site is near Kaena Ridge, observed to generate intense internal tides (Nash et al, ), it is likely that the measured pressure gradients and the resulting velocities are primarily driven by the evanescent tail of the M 2 internal tide propagating in deeper stratified waters offshore, which influences the nearshore region, despite the lack of local stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Diurnal internal tides north of Hawaii are not energetic, however (Dushaw et al., 2011), but see Smith et al. (2017). Future avenues of research may be to determine the evolution of the diurnal tidal field eastward across the Atlantis, or to examine internal‐wave‐admitting simulations for the wind‐forced equatorial internal waves of Wunsch and Gill (1976).…”
Section: Discussionmentioning
confidence: 99%
“…Other than perhaps the Hawaiian Ridge, which extends across 24°N, similar configurations, that is, a substantial topographic feature equatorward of internal-tide turning latitudes that might support resonance, do not exist elsewhere; the Sargasso Sea is unique. Diurnal internal tides north of Hawaii are not energetic, however (Dushaw et al, 2011), but see Smith et al (2017). Future avenues of research may be to determine the evolution of the diurnal tidal field eastward across the Atlantis, or to examine internal-wave-admitting simulations for the wind-forced equatorial internal waves of Wunsch and Gill (1976).…”
Section: Discussionmentioning
confidence: 99%
“…Müller (2013) estimated that the global energy conversion by M 2 , S 2 , K 1 and O 1 to be 1.11 (66%), 0.19 (11%), 0.24 (14%) and 0.13 TW (8%) respectively. The contribution of the K 1 diurnal tide alone has been reported from 8% to 50% of M 2 conversion in Luzon Strait and over Hawaiian Ridge (K. Liu et al., 2017; Smith et al., 2017). Moreover, the interaction of M 2 with other tidal constituents (such as K 1 and O 1 ) over ridges and continental slopes can (a) evoke higher frequency elements in the system, (b) affect the energy conversion rate, and (c) increase the energy dissipation locally through nonlinear interactions (Guo et al., 2020; Liu et al., 2015; X. H. Xie et al., 2008; X. Xie et al., 2010).…”
Section: Introductionmentioning
confidence: 99%